ASSESSMENT OF SLEEP QUALITY DURING WINTER SEMESTER IN UNDERGRADUATE MEDICAL STUDENTS ENROLLED AT UKIM, FACULTY OF MEDICINE, SKOPJE, REPUBLIC OF NORTH MACEDONIA - Mancevska, Sanja; Pislevski, Matej; Pluncevic Gligoroska, Jasmina (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
The aim of the study was to assess sleep quality in medical students from all study years enrolled at Faculty of Medicine, UKIM, Skopje during winter semester of the academic year 2022/23. An online survey including the Pittsburgh Sleep Quality Index (PSQI) and a questionnaire regarding demographic variables (age and gender) was available via Google Forms to a cohort of students at three time points (the beginning, the middle and the end) of the winter semester. A total of 113 students from all years, aged 18-28, responded. Eighty percent of them were female and 20% were male.  The PSQI is a self-report questionnaire that assesses overall sleep quality during an one month time interval. It consists of 19 questions regarding subjective sleep quality, the latency, duration, efficiency of sleep, sleep disorders, the use of sleep medications and daytime dysfunction. A total PSQI score can be calculated and it ranges from 0 to 21 with a higher score indicating poorer sleep quality. The mean value of the total PSQI score increased from the first to the third time point of the study (7.8 Â±3.3; 8.1Â±3.4; 8.4Â±3.5 respectively) (p=0.172). More than 60% of the students (62.2%; 63.7%; 64.1% respectively) showed poor sleep quality (PSQI >5), with 31% using sleeping medication. Sleep duration in 75% of students was shorter than 7 hours, with 11% sleeping less than five hours. A reduction in overall sleep quality can be observed in medical students during the winter semester. Keywords: sleep quality, PSQI, medical students